Pendidikan Islam di Era Digital - Sugiyarti, Sri; Anshory, Muhammad Isa (TSAQOFAH, 2024)
This article explores the role and transformation of Islamic education from the colonial period to the era of independence, then details the significant changes that occurred with the advent of the digital era. A thorough analysis of how Islamic education is adapting to modern technology is the focus, taking into account emerging challenges and opportunities.